Russia is Back to the Balancing Game - Samet YÜCE; Philipp O. AMOUR (Gazi Akademik Bakış)
This research mainly aims to show the balancing game of Russia in Syria and Libya after the Arab Spring. Recently Russia has increased its influence in Syria and Libya by its own capabilities and alliances with regional and local actors. Thus, it sought to consolidate its strength and balance its rivals, predominantly the US, in the international system. After the Arab Spring, Russia deployed its military muscle to Syria to protect its traditional ally the Bashar al-Assad regime, and restrain the US from solely dominating the region. Its attempts achieved to ensure the regime’s survival and balance the US in the country. Later, it sought to expand its sphere of influence and balance the rivals in Libya. It primarily used its own capabilities and alliance relations with the Khalifa Haftar group, the UAE, and Egypt. Russia’s growing presence in Libya inevitably affected the regional competition and balance of power among the states. However, the clashes among the militias supported by the external powers escalated in the fragmented country. Eventually, the UN-recognized GNA consolidated its power against the Khalifa Haftar forces and seized the control of northwest Libya, but an unstable environment still prevails in the country.